Pathogenic variability in Fusarium udum isolates causing pigeonpea wilt - Sinha, P; Kadu, L N; Dhandapani, A; Jite, P K; Dhar, Vishwa (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2004-07 to study pathogenic variability in Fusarium udum Butter isolates causing pigeonpea wilt. A population of 69 isolates collected from 4 northern states was grouped in 18 types based on cultural and morphological characters, such as sporulation, mycelial colour, in-vitro growth rate, length and number of septa of macroconidia. These 69 isolates could be grouped in 3 types, such as highly, moderately and slow or weakly pathogenic. Linear discriminant functions could explain group variation only for moderately and slow pathogenic types. DNA amplification pattern indicated that an array of highly and moderately pathogenic isolates recovered from various pigeonpea cultivars and sites of northern India produced almost identical patterns. Highly and moderately pathogenic isolates examined were almost identical for a large number of loci in comparison to slow pathogenic type.